2015
DOI: 10.19082/1590
|View full text |Cite
|
Sign up to set email alerts
|

Would Phoenix Dactyflera Pollen (palm seed) be considered as a treatment agent against Males’ infertility? A systematic review

Abstract: IntroductionOxidative stress is a key factor involved in male infertility, which is due to an unnatural increase in environmental free radicals. In the majority of cases, this has a negative effect on a male’s ability to impregnate a female. Currently, it is believed that spermatozoa can be protected against the damages induced by oxidative stress by saturating sperm with antioxidants. The antioxidant role of phoenix dactylifera pollen is capable of collecting the reactive oxygen and neutralizing it in and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
0
12
0
3
Order By: Relevance
“…Arginine, one of the main amino acids in the drug (9), acts as an antioxidant in the empirical treatment of idiopathic male infertility (4). A systematic review has highlighted its effects on improving semen parameters caused by the impact on the antioxidant system (18).…”
Section: Discussionmentioning
confidence: 99%
“…Arginine, one of the main amino acids in the drug (9), acts as an antioxidant in the empirical treatment of idiopathic male infertility (4). A systematic review has highlighted its effects on improving semen parameters caused by the impact on the antioxidant system (18).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatotoxicity induced by various chemicals was reversed by Phoenix dactylifera [18,19]. It is also found to be effective in diabetes [20], male infertility (seeds) [21,22], inflammation, and bacterial infection [23]. Moreover, cardioprotective [24] and antioxidant actions [25] are also reported widely.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, various in vitro and in vivo experimental studies, and clinical trials, have evaluated the effects of DPP on the reproductive system. All research indicates that there are significant improvements in the sperm parameters, such as motility, viability, acrosome reaction, and lipid peroxidation (Fallahi et al 2015). Al-Samarrai et al (2017) have found a higher fertility on rabbit bucks after orally administration of DPP suspension, which enhance the production of testosterone and increase the spermatogenesis.…”
Section: Introductionmentioning
confidence: 98%
“…DPP is known to contain a variety of compounds such as a high concentration of total phenolic content, flavonoids and anthocyanins as well as the presence of significant quantity of selenoproteins (Baliga et al 2011) which makes it an excellent candidate for antioxidant activity associated to low negative side effects (Fallahi et al 2015). Thus it is a very suitable supplement in infertility particularly by reducing free radicals and enhancing sperm motility (Fallahi et al 2015). Therefore, synergic beneficial effect of bioactive compounds along with antioxidant activity of DPP extract might result to improved properties of spermatozoa.…”
Section: Introductionmentioning
confidence: 99%